Development of a clinical measurement tool for measuring voluntary eye movements in typical infants six months of age - Uys, C.J.E. (Catharina Jacoba Elizabeth) (University of Pretoria, 2023)
Thesis (PhD (Occupational Therapy))--University of Pretoria, 2022.